(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Background: The prevalence of childhood obesity increasing steadily in India. Obesity may results from a complex interaction of endogenous and exogenous causes. Most of them having exogenous causes and physical inactivity is one of them. Increased hours of inactivity due to increasing academic pressure, use of electronics gazettes have all replaced outdoor games and activities which promotes sedentary life. There are very few studies describing the pattern of physical activity of children in India. Aim: The present study aimed to find out correlation between physical activity, BMI and time spend in front of screen among children. Methodology: Study was approved by review board of ethics committee. 312 school going children of various income groups with the age 6-12 years were recruited by purposive sampling method. Informed consent was provided by teachers or parents. Height and weight of children was taken to calculate BMI. Physical Activity Questionnaire for children (PAQ-C) was filled up to assess the physical activity by children. Self-reported hours of time spent in front of the screen was noted. Results: Distribution of obesity and overweight in the sample was 9% and 16%, respectively. There were statistically significant negative correlation between physical activity and BMI (r = -0.619); and Time Spend in front of Screen and physical activity (r = -0.554). There was positive correlation between BMI and Time Spend in front of Screen (r= 0.556). Conclusion: Increasing prevalence of overweight and obesity in school going children relate to decreasing physical activity level and increasing time spend if front of TV, video games and computers.